Legal status of youth councils in Poland and France in the light of new legal regulations - Augustyniak, Monika (Review of European and Comparative Law, 2022)
The subject of the paper is the legal status of consultative bodies dedicated to young people, which are established both in the Polish local government and in the French local government community. In both legal orders these bodies have a consultative and advisory character. However, there are some differences in their structure and forms of action, which may constitute a field of reflection on their legal status. In Poland and in France, there is a noticeable trend towards expanding the importance and tasks of these bodies in self-governing communities, which indicates a good direction of change. Due to an increase in civic awareness, youth structures in Polish and French local government are becoming an essential element in the creation of democratic administrative structures.